Las fumigaciones aéreas y su incidencia en las enfermedades epidérmicas en los trabajadores agrícolas que laboran en la hacienda los cerritos del cantón Puebloviejo durante el primer semestre del 2013 - Cuenca Zambrano, Carolina Cecibel (2013)
The contamination constitutes one of the most serious environmental problems around the world. Many factors contribute to the aggravation of this situation. One of the most alarming is the use of pesticides for the control of insect pests in agricultural crops. Principio del formulario Agricultural workers are exposed to the effects of these aerial spraying. Many times due to ignorance and other negligence of them and their heads. In addition, the lack of training to farmers for the management, implementation and provision of the agrochemicals and food containers next to the correct disposal of waste of the spraying and the breach of the rules of protection, aggravates the problem. Through this work was carried out a survey to a representative sample of agricultural workers of the Hacienda Cerritos with the aim of determining the degree of incidence of the aerial spraying in the epidermic diseases in farm workers working in the finance of the Canton of Los Cerritos Pueblo Viejo, in the first half of 2013. Principio del formulario The majority of the respondents said that one of the causes by which are skin diseases is lack of knowledge about the measures of protection and the damage that produce pesticides to human health.